P083 High prevalence of ulcerative appendicitis in UC patients without colonic disease activity. (27th May 2021) - Heuthorst, L; Mookhoek, A; Wildenberg, M; D'Haens, G; Bemelman, W; Buskens, C
Abstract: Background: The aim of the current study was to assess histological features of appendices from patients with UC and its clinical relevance. Methods: Patients with UC in remission and active UC (therapy refractory) that underwent an appendectomy in the frame of clinical trials between 2012–2019 were included. Histological features of UC appendices were compared to those of patients with acute appendicitis and colon carcinoma. The Robarts Histopathology Index score (RHI) was used to assess appendiceal inflammation. In patients with active UC, clinical and histological characteristics were compared between patients with and without endoscopic response after appendectomy. Results: In total, 140 appendix specimens were assessed (n=35 UC remission, n=35 active UC, n=35 acute appendicitis, n=35 colon carcinoma). Histological features of appendices from UC patients looked like UC rather than acute appendicitis. The incidence of active appendiceal inflammation was not different between UC patients in remission versus active disease (53.7% versus 46.3%, p=0.45) and limited versus extensive disease (58.5% versus 41.5%, p=0.50). Endoscopic response, assessed in 28 therapy refractory patients, was more frequently seen in patients with higher RHI scores (RHI>9 81.8% versus RHI≤9 9.1%, p=0.004) and limited disease (proctitis/left sided 63.6% versus pancolitis 36.4%, p=0.02). Conclusion: The presence of active appendiceal inflammation is common in UC and not related to disease activity in the colon. More than 50% of UC patients in remission show active histological disease in the appendix. Favorable response to appendectomy for refractory UC was seen in cases with ulcerative appendicitis. These findings might support the role of the appendix as a driving force in UC.